The Role of The Three Pillars of Community Strengthening at The Grassroots in Realizing Social Order - Satibi (Jurnal Ilmiah Hukum dan Keadilan, 2026)
Social order is a condition formed through social interactions based on norms, values, and cooperation among social actors. In Kopo Sub-district, social order is established through synergy between the government and the community, driven by three pillars, namely the Sub-district Leadership Coordination Forum (Forkopimcam). This synergy plays an important role in creating a harmonious, safe, and conducive social environment through effective communication and coordination. This study aims to analyze the role of the three pillars in realizing social order at the grassroots level. The research employs a normative juridical method with a descriptive-analytical approach, utilizing primary, secondary, and tertiary data. The findings indicate that the role of Forkopimcam as the three pillars is strategic in the early detection and management of potential social conflicts. However, the success of these efforts largely depends on active community participation, including religious leaders, community leaders, youth leaders, and other societal elements. The presence of Forkopimcam in various community activities strengthens public trust and encourages community involvement in maintaining social order.